Effects of multivitamin, mineral and herbal supplement on cognition in younger adults and the contribution of B group vitamins. (January 2014) - Pipingas, Andrew; Camfield, David A.; Stough, Con; Scholey, Andrew B.; Cox, Katherine H.M.; White, David; Sarris, Jerome; Sali, Avni; Macpherson, Helen
<x xml:space="preserve">Abstract</x> Objective Cognitive benefits of multivitamins have been observed in the elderly, but fewer trials have investigated younger, healthy cohorts. This randomised, double‐blind, placebo‐controlled study investigated the cognitive effects of 16‐week multivitamin supplementation in adults aged 20–49 years. Method A total of 138 participants aged 20–50 years were randomised and 116 completed the trial. The participants completed a computerised battery of cognitive tasks before and after 16‐week supplementation with a multivitamin containing minerals and herbs or placebo. Blood measures of homocysteine, vitamin B6, B12 and folate were collected at both time points. Results In men, there was a strong trend (p = 0.01; which did not reach significance when adjusted for multiple comparisons) for the multivitamin to improve performance on the incongruent stroop task, a measure of selective attention and response inhibition. There were no cognitive benefits of multivitamin supplements in women. Multivitamin supplementation substantially increased blood levels of vitamin B6, B12 and folate in both genders and decreased homocysteine in men. In men who received the multivitamin, improved stroop congruent performance was associated with increased vitamin B6 levels. Conclusion Multivitamin supplementation may be useful for maintaining levels of B vitamins. The effects of multivitamins on speeded attention such as the stroop task in young adults warrant further investigation. Copyright © 2014 John Wiley & Sons, Ltd.